A Symmetric All‐Organic Proton Battery in Mild Electrolyte. (29th December 2021) - Tie, Zhiwei; Deng, Shenzhen; Cao, Hongmei; Yao, Minjie; Niu, Zhiqiang; Chen, Jun
Abstract: All‐organic proton batteries are attracting extensive attention due to their sustainability merits and excellent rate capability. Generally, strong acids (e.g. H2 SO4 ) have to be employed as the electrolytes to provide H + for all‐organic proton batteries due to the high H + intercalation energy barrier. Until now, the design of all‐organic proton batteries in mild electrolytes is still a challenge. Herein, a poly(2, 9‐dihydroquinoxalino[2, 3‐b]phenazine) (PO) molecule was designed and synthesized, where the adjacent C=N groups show two different chemical environments, resulting in two‐step redox reactions. Moreover, the two reactions possess considerable voltage difference because of the large LUMO energy gap between PO and its reduction product. More impressively, the C=N groups endow the π‐conjugated PO molecule with H + uptake/removal in the ZnSO4 electrolyte. As a result, a symmetric all‐organic proton battery is achieved in a mild electrolyte for the first time, which exhibits enhanced electrochemical performance and also broadens the chemistry of proton‐based batteries. Abstract : A symmetric all‐organic proton battery is developed in mild ZnSO4 electrolyte, which exhibits enhanced electrochemical performance and broadens proton‐based battery chemistry.